The Connection between Phrases and Linguoculture in Comparative Study - Maktuba Mahamadalievna Khonsaidova (Zien Journals, 2024)
The correlation of phrases with linguoculture in a comparative study is a fascinating area of research within linguistics. Phrases are linguistic units that consist of two or more words whose meaning is different from the literal interpretation of the individual words. These compounds often carry cultural connotations and reflect the values, beliefs, and customs of a particular linguistic community. In a comparative study, researchers can analyze how phraseological compounds vary across different languages and cultures, shedding light on the unique ways in which each culture expresses ideas and concepts. By examining the use of phraseological compounds in various cultural contexts, researchers can gain insights into the underlying values and norms of different societies. Studying the correlation of phrases with linguoculture in a comparative framework can provide valuable insights into the intricate relationship between language and culture, enriching our understanding of both linguistic diversity and cultural identity
Keywords: Linguoculture; phrases; phraseological compounds; comparative study